Tracking the origin of civil engineering as a science since ancient times - Elena V. Sysoeva (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. The gradual progressive evolvement of civil engineering as a science was nurtured by numerous discoveries, errors and regularities contributed by philosophers, mathematicians, engineers, architects, and researchers focused on versatile areas of knowledge. The author analyzes the transformation of civil engineering as a science since ancient times, as well as its dependence on historical events, territoriality, and discoveries. The objective of the research, covered by the article, consists in the detailed analysis of the history of civil engineering and the prognostication of its future development pattern.Materials and methods.The author employed systematization, benchmarking, and theoretical generalization of the information collected from literary sources.Results. The author has analyzed a number of Russian and foreign literary sources covering the formation and evolution of the civil engineering science, beginning with the works of ancient thinkers and philosophers and ending with the works of contemporary researchers. The author breaks down the history of analysis/design of buildings/structures into four development phases that have evolved into the present-day design procedure. The author also provides detailed information on ancient scholars, starting from those who lived in the second millennium B.C., and their contribution into the theory of building design. She highlights the most important works written by ancient philosophers and mathematicians all over the world, particularly those who influenced the development of the design theory. The author provides examples and photos of still-standing unique buildings and structures that date back to each development phase. Every step of civil engineering development is illustrated by buildings and descriptions of their constructions. The author also analyzes the most prominent attainments made in the field of structural mechanics and design of buildings at each development stage. She has tracked the evolvement of civil engineering since the inception of written languagest.Conclusions. The author analyzes the prospects for the development of the civil engineering science with account for the most recent reports issued by the Russian Academy of Architecture and Construction Sciences.